Bridging constitutional dignity and environmental rights jurisprudence. Issue 2 (September 2016) - Daly, Erin; May, James R
Abstract : Rights to human dignity and to environmental quality have evolved co-incidentally, if independently, as drivers in modern constitutionalism. Most constitutions recognize a right to a quality environment, a right to human dignity, or both. Both rights are relatively recent inventions, and few – if any – modern constitutions are adopted or amended without attention to both of these features. Moreover, they share commonalities, inter alia, related to identifying causes of action, appropriate parties, and the scope of judicial review and remedies. And both involve complex legal, philosophical, and political dimensions. Notwithstanding such positive correlations, courts from around the globe have been considerably more inclined to engage constitutionalized rights to human dignity than constitutionalized rights to a quality environment. Moreover, jurists, advocates and scholars have tended to overlook or ignore threads entwining human dignity and environmental rights jurisprudence. This article aims to tie up these loose ends. After sampling both dignity and environmental rights jurisprudence and then examining the associations between the two, this article concludes that environmental and dignity rights jurisprudence can correspond in more mutually complementary ways. First, dignity can play a more prominent place in judicial treatment of environmental rights. Second, dignity rights jurisprudence can do more to engage the ways in which environmental degradation diminishes human dignity. As the two areas develop in tandem, jurisprudential outcomes in each area stand to benefit.